Activating activism: Facebook trending topics, media franchises, and industry disruption. Issue 2 (15th March 2017) - Johnson, Derek
ABSTRACT: This research considers the politics of the Facebook platform and the paratextual role of its Trending Topics module in opening the door to #FranchiseActivism: calls for intervention in the media industries' management and exploitation of specific entertainment properties, organized and mobilized on social media, in which future representations, labor practices, and market priorities for ongoing media franchises often become articulated to the pursuit of social justice. Trending Topics goes beyond enabling activism by selecting, ordering, and organizing its expressions alongside the industrial forms of publicity and promotion also circulating in users' news feeds. Facebook can alternately push activist conversations about media franchising to the forefront of social media discussion of major entertainment industry franchises or suppress it in favor of celebratory promotional narratives preferred by studio marketers. That Facebook opens doors to activist critique of franchising and puts media industries on the defensive (even as it simultaneously points to their preferred promotional gateways) speaks to the power Facebook algorithms have to shape the field of paratextual possibility. At the same time, human curatorial agency and corporate imperatives impose themselves upon algorithms to privilege the activation of activist perspectives within the hype of media franchising. Ultimately, this research identifies Facebook as a paratextual platform, considering the ways Trending algorithms enable and limit paratextual experiences, specific instances in which Trending Topics privilege activist intertexts alongside studio promotion of major media franchises, as well as the institutional priorities shaping Facebook's management of this paratextual work. In activating activism in its Trending Topics, the Facebook platform opens the door to critical engagements with media franchising while demonstrating a paratextual framing power that can disrupt the patterns of hype constructed by entertainment media industries.